Comorbidities of Idiopathic Thrombocytopenic Purpura: A Population-Based Study. (5th January 2009) - Feudjo-Tepie, M. A.; Le Roux, G.; Beach, K. J.; Bennett, D.; Robinson, N. J.
Abstract : A person experiencing more than one medical condition may have ambiguous clinical presentation. ITP is a serious autoimmune disease with little epidemiological evidence on its burden, risk factors, and comorbidities. Using the United Kingdom general practice research database, we conducted a 14 years population-based case control-type study to explore medical conditions more likely to cooccur with ITP and their temporal relationship in association with ITP. ITP patients were matched to non-ITP on practice, age, gender, and follow-up period. Potential comorbidities were represented by patients' medical information at the preferred term level of the MedDRA international classification. As well as death (OR = 60.0 ; 95% CI [4.47–806.0]) and known clinical signs and symptoms of ITP, ITP is associated with considerable number of medical conditions. The association between ITP and some of these conditions is apparent both before and after ITP diagnosis. Specific targeted studies can now be setup to reexamine observed associations.